Exploring the Impact of Robotics-Based Learning on Students' Emotional Intelligence and Academic Achievement: A Semi-Experimental Study - Leila Ahmadzadeh; Kausar Dashti Moghadam (Interdisciplinary Journal of Virtual Learning in Medical Sciences)
Background: Nowadays, the advancement and integration of new technologies in educational settings have emerged as significant and complex challenges. Among these innovations, Robotic-based Learning (RBL) has garnered considerable interest from researchers and educators alike. This study aimed to explore the impact of RBL on students' Emotional Intelligence (EI) and Academic Achievement.Methods: This semi-experimental study employed a pretest-posttest design featuring two groups: an intervention group that underwent training using the RBL method and a control group that received traditional training. The research was carried out at a secondary school in Behbahan City, Iran, from September 2022 to May 2023. A total of 30 eligible students were selected through a convenience sampling method, with 15 randomly assigned to the intervention group and 15 to the control group. A learning achievement test comprising 20 open-ended questions covering various mathematical domains was administered as a pre-test in September 2022 and again as a post-test immediately after the intervention in May 2023. Additionally, the Brief Emotional Intelligence Scale (BEIS-10) was employed to evaluate the emotional intelligence (EI) of the students. Data analysis was performed using analysis of covariance and independent samples t-tests, utilizing SPSS version 24, with a significance threshold set at a P-value of less than 0.05.Results: The results indicated that RBL has a significant effect on students' EI and sub-dimensions of self-motivation (P=0.081), self-awareness (P<0.001), self-control (P=0.061), social awareness (P<0.001), and social skills (P=0.003). Also, the results of the ANCOVA test comparing the pretest and posttest of both intervention and control groups revealed a significant effect of RBL on the students' learning achievements (P<0.001).Conclusion: The findings of this study indicate that RBL is an effective instructional approach for enhancing both student achievement and EI among first-year secondary students.